2011
DOI: 10.1084/jem.20110198
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling inhibits hepatocellular carcinoma following inactivation of the RB pathway

Abstract: Mice lacking all three Rb genes in the liver develop tumors resembling specific subgroups of human hepatocellular carcinomas, and Notch activity appears to suppress the growth and progression of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(169 citation statements)
references
References 82 publications
5
162
1
1
Order By: Relevance
“…14 Notch1 signaling therefore seems to have a crucial role. Notch1 signaling also appears to have tumor suppressor roles in murine keratinocytes, 20 human pancreatic 19 and hepatocellular carcinomas 18 and small-cell lung cancer. 33 Taken together, these observations indicate that aberrant activation of the Notch1 pathway has various roles in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Notch1 signaling therefore seems to have a crucial role. Notch1 signaling also appears to have tumor suppressor roles in murine keratinocytes, 20 human pancreatic 19 and hepatocellular carcinomas 18 and small-cell lung cancer. 33 Taken together, these observations indicate that aberrant activation of the Notch1 pathway has various roles in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 On the other hand, there is growing evidence that Notch signaling activation may have growthsuppressive functions in other hematopoietic cells, hepatocytes, the pancreatic epithelium and skin. [17][18][19][20] Several studies have indicated that upregulation of Notch signaling may contribute to the malignant phenotype in head and neck squamous cell carcinomas (HNSCCs), including those of the oral cavity. 21,22 However, some researchers have shown that Notch signaling has a tumor suppressive role.…”
mentioning
confidence: 99%
“…Patients with better survival showed significantly higher expression of Notch related genes (33). Two recent studies of head and neck squamous cell carcinoma identified mutation affecting Notch receptors.…”
Section: Notch As a Tumor Suppressor In Solid Tumorsmentioning
confidence: 95%
“…Accordingly, in CCA development, N1ICD association with protein kinase B signaling in hepatocytes stimulated their malignant dedifferentiation (82). The stimulation of N1ICD expression by inflammatory mediators has also been reported in human CCA, which additionally supports the role of Notch in liver cancer (83) (Table II) (9,12,24,31,(84)(85)(86)(87).…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 59%